In-hospital falls and fall-related injuries: a protocol for a cost of fall study. - Morello, R.; Barker, A.; Haines, T.; Zavarsek, S.; Hill, Keith; Brand, C.; Sherrington, C.; Wolfe, R.; Bohensky, M.; Stoelwinder, J. (BMJ Publishing Group, 2013)
BACKGROUND: In-hospital falls are common and pose significant economic burden on the healthcare system. To date, few studies have quantified the additional cost of hospitalisation associated with an in-hospital fall or fall-related injury. The aim of this study is to determine the additional length of stay and hospitalisation costs associated with in-hospital falls and fall-related injuries, from the acute hospital perspective.METHODS AND DESIGN: A multisite prospective study will be conducted as part of a larger falls-prevention clinical trial—the 6-PACK project. This study will involve 12 acute medical and surgical wards from six hospitals across Australia. Patient and admission characteristics, outcome and hospitalisation cost data will be prospectively collected on approximately 15 000 patients during the 15-month study period. A review of all in-hospital fall events will be conducted using a multimodal method (medical record review and daily verbal report from the nurse unit manager, triangulated with falls recorded in the hospital incident reporting and administrative database), to ensure complete case ascertainment. Hospital clinical costing data will be used to calculate patient-level hospitalisation costs incurred by a patient during their inpatient stay. Additional hospital and hospital resource utilisation costs attributable to in-hospital falls and fall-related injuries will be calculated using linear regression modelling, adjusting for a priori-defined potential confounding factors.DISCUSSION: This protocol provides the detailed statement of the planned analysis. The results from this study will be used to support healthcare planning, policy making and allocation of funding relating to falls prevention within acute hospitals.